Analysis of Inclusive Education Services in Early Childhood Education Institutions of the PESAT Foundation in Central Java - Harefa, Ida Destariana; Diana, Diana; Pranoto, Yuli Kurniawati Sugiyo (JURNAL PENDIDIKAN USIA DINI, 2025)
Inclusive education in Early Childhood Education aims to ptovide equal opportunities fot children with special needs to be able to learn with other children and develop their potential from an early age. This study aims to examine inclusive education servises in the Early Childhood Education of the PESAT Foundation in Central Jawa, focusing on five kindergartens: TK Kristen Pniel Terpadu, TK Kristen Imanuel Terpadu, TK Kristen Benih Kasih Terpadu, TK Kristen Petra Terpadu, and TK Kristen Sion Tridamarsari. This study uses a type of quantitative research with questionnaires as a data collection tool. The data analysis method use in this study is a SWOT analysis conducted with EFAS and IFAS calculations. This includes shecking Strengths, Weaknesses, Opportunities, and Threats. The results of the study can be obtained by conducting a SWOT analysis based on IFAS and EFAS, followed by calculations using AFE and IFE. The Results of the study obtained results with this SWOT approach, the position of Early Childhood Education of the PESAT Foundation in Central Jawa is in quadrant I, namely using a growth (growing) strategy. This position indicates the application of a growth strategy or a progressive strategy. Based on the results obtained, it can be concluded that inclusive education services implemented by schools have greater strengths than weaknesses and greater opportunities than treats, thus supporting progressive growth policie.